TMIC-18. ELECTRICAL CIRCUIT INTEGRATION OF GLIOMA THROUGH NEURON-GLIOMA SYNAPSES AND POTASSIUM CURRENTS. (11th November 2019) - Venkatesh, Humsa; Morishita, Wade; Geraghty, Anna; Silverbush, Dana; Gillespie, Shawn; Arzt, Marlene; Tam, Lydia; Ponnuswami, Anitha; Ni, Lijun; Woo, Pamelyn; Taylor, Kathryn; Agarwal, Amit; et al.
Abstract: High-grade gliomas are a lethal group of cancers whose progression is robustly regulated by neuronal activity. Activity-regulated release of growth factors into the tumor microenvironment represents part of the mechanism by which neuronal activity influences glioma growth, but this alone is insufficient to explain the magnitude of the effect that activity exerts on glioma progression. Here, we report that neuron-glioma interactions include electrochemical communication through both bona fide synapses and activity-dependent potassium flux. Single cell transcriptomic analyses revealed unambiguous expression of synaptic genes by malignant glioma cells, and neuron to glioma synaptic structures were evident by electron microscopy. Whole cell patch clamp electrophysiology demonstrated AMPAR-mediated excitatory neurotransmission between pre-synaptic neurons and post-synaptic glioma cells. Millisecond timescale excitatory post-synaptic currents (EPSCs) were found in a subpopulation of glioma cells, reminiscent of the axon-glial synapses between neurons and normal oligodendrocyte precursor cells (OPCs). Neuronal activity also evokes a second, non-synaptic electrophysiological response characterized by a prolonged (>1 sec) depolarization in a subpopulation of glioma cells. These longer duration currents are blocked by tetrodotoxin or barium and induced by potassium, indicating neuronal activity-dependent potassium flux reminiscent of astrocyte currents. The amplitude of the prolonged currents is reduced by gap junction inhibitors, supporting the concept that gap junction-mediated tumor interconnections can function to amplify evoked potassium currents in an electrically coupled network. As membrane depolarization of normal neural precursor cells can regulate proliferation, differentiation and survival, and glioma cells exhibit two distinct mechanisms of neuronal activity-evoked membrane depolarization, we tested the hypothesis that membrane depolarization promotes glioma growth. Using in vivooptogenetic techniques to depolarize xenografted glioma cells, we found that glioma membrane depolarization robustly promoted proliferation, while pharmacologically or genetically blocking electrochemical signaling inhibited glioma xenograft growth and extended mouse survival. Together, these findings indicate that electrical circuit integration promotes glioma progression.